2017
DOI: 10.3390/rs9030228
|View full text |Cite
|
Sign up to set email alerts
|

Inverting Aboveground Biomass–Canopy Texture Relationships in a Landscape of Forest Mosaic in the Western Ghats of India Using Very High Resolution Cartosat Imagery

Abstract: Large scale assessment of aboveground biomass (AGB) in tropical forests is often limited by the saturation of remote sensing signals at high AGB values. Fourier Transform Textural Ordination (FOTO) performs well in quantifying canopy texture from very high-resolution (VHR) imagery, from which stand structure parameters can be retrieved with no saturation effect for AGB values up to 650 Mg·ha −1 . The method is robust when tested on wet evergreen forests but is more demanding when applied across different fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…This is likely due to the strong correlation coefficients between the forest AGB and SVI, NDVI, and RVI, which are consistent with the results from the scatterplots ( Figure 5). The result was in line with recent study results reported in Shen et al [88] and Pargal et al [89]. Our results suggest that SVI, NDVI, RVI, and PCA1 generated from Sentinel-2A data play an important role in the forest AGB estimation compared to other vegetation indices in the study area.…”
Section: The Role Of the Predictive Variablessupporting
confidence: 93%
“…This is likely due to the strong correlation coefficients between the forest AGB and SVI, NDVI, and RVI, which are consistent with the results from the scatterplots ( Figure 5). The result was in line with recent study results reported in Shen et al [88] and Pargal et al [89]. Our results suggest that SVI, NDVI, RVI, and PCA1 generated from Sentinel-2A data play an important role in the forest AGB estimation compared to other vegetation indices in the study area.…”
Section: The Role Of the Predictive Variablessupporting
confidence: 93%
“…). The performance of such texture‐based metrics to infer forest AGB has been shown to vary strongly among sites and forest types (Pargal et al., 2017; Ploton et al., 2017; Ploton et al., 2013) and to be highly dependent on image acquisition parameters (Barbier et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Two very popular textural measures used as a remotely sensed vegetation structure feature are the grey-level co-occurrence matrix (GLCM) texture 3942 and Fourier transform textural ordination (FOTO) 20,4345 . Although textural features have been applied to various sensors such as IKONOS-2 42 , Cartosat-1a 46 , SPOT-5 41 , QuickBird 47,48 , WorldView-2 49 , or RapidEye 21 , it was not tested on how it performs using Planet Dove images for large scale mapping of ACD.…”
Section: Introductionmentioning
confidence: 99%